Personalized electronic medical records - Yong, Jun Jie. (2010)
Singapore is found to be among the top ten in world’s fastest aging population [1]. This is due to factors like low birth rates and high life expectancy. To meet the increase need to provide better healthcare services to these elderly and also to position Singapore itself as a medical hub, more doctors and nurses are needed from the already shrinking workforce. In the face of this scenario, robots can help to take over some of the more mundane and routine works in the hospitals, thus allowing the hospital staff to focus more on other areas which requires the human touch. In this light, this project shall address this issue with the prototype of a controllable robot, which will assist doctors and nurses at bedside. As the robotic hardware and firmware is developed by another team, this report shall focus only on the software capabilities. The aim of the software is to provide both robotic and clinical functions. The robotic function shall consist of a Graphical User Interface to control the firmware of the robot while the clinical functions shall streamline clinical processes by rapidly and selectively present and update information at bedside.